PROSES DESTINATION BRANDING DALAM MEMBENTUK CITRA TUJUAN WISATA MUSEUM INDONESIA - Hereyah, Yoyoh; Kusumaningrum, Rastri (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2019)
Museum tourist developments in Indonesia continued to show seriousness in efforts utilization as a public space with active people involvement in the museum activities, especially community. However, views on the museum is fashioned, old, boring and spooky still dominant in the society. This study further to see how the collaboration between government and the community in doing destination branding in order to change society's view so as to form a positive image destination stronger. The goal is to analyze the implementation of destination branding by the community through exposure program to finally persuade others to contribute actively in destination branding by using elaboration likelihood models. How the program’s exposure by the community contribute to the process of destination branding museum tourism? How community members elaborate the persuasion messages in the exposure program if analyzed using the elaboration likelihood model theory? The method used is by interview and search for document data from the Komunitas Jelajah Budaya. The results showed that the application of the destination branding museum tourism of Indonesia by the Komunitas Jelajah Budaya with providing message exposure from Program Jelajah Kota Toea and Night Time Journey At The Museum more emphasis on personal approach, word of mouth and packaging programs that persuade people who have the motivation and the need for the message, which is then analyzed using the elaboration likelihood model and show the path difference receiving messages through the central and peripheral factors these different motivations, needs and ability to evaluate the message which then forms a change in attitude. The author recommends to make persuasive messages that more interesting in publishing community programs so the main message in process of destination branding of museum tourism can be elaborated properly by visitors or community members.